Polimorfismos dos genes apolipoproteínas E e A5 e relação com parâmetros bioquímicos e hemostáticos em dislipidêmicos - Claudia Natalia Ferreira (2010)
Atherosclerosis is a complex process due to multiple genetic and environmental interactions that modify not only lipid metabolism but also the coagulation system and inflammatory response. Dyslipidemia is the most important risk factor for atherosclerosis, predisposing to cardiovascular disease. The aim of this study was to describe the allelic and genotypic distribution of the APOE and APOA5 -1131T>C polymorphisms and their relationship with lipid-lipoprotein plasma levels and hemostatic parameters in both dyslipidemic patients and normolipidemic subjects. The study included 216 individuals, distributed into 2 sub-groups, including 109 dyslipidemic subjects (41 women and 68 men, with a mean age of 48.4 ± 6.8 years) and 107 normolipidemic healthy volunteers (63 women and 44 men; mean age: 46.7 ± 6.6 years). Lipid levels were classified according to the Brazilian Society of Cardiology 2001. The frequencies of alleles and genotypes for the APOE polymorphism were homogenous between groups. As it was analysed the effect of APOE polymorphism on lipid levels in dyslipidemic and normolipemic groups, no significant differences were observed among E2, E3 and E4 and plasma lipid-lipoprotein levels in the dyslipidemic group. However, in the normolipidemic group, total cholesterol, LDLc and non-HDLc plasma levels were significantly lower in E2 patients compared to 3 and 4 (E2 < E3 = 4, p < 0.05). It was also described that in dyslipidemic subjects, 2 allele carreers showed increased TAFI levels when compared to 4 allele carreers. The frequencies of C allele and TC genotype of the APOA5 -1131T>C polymorphism in dyslipidemic subjects were significantly higher than those observed in normolipidemic group. When data were analyzed distributing all participants in the 2 APOA5 sub-groups T (TT genotype) and C (TC and CC genotypes), the rare allele APOA5 -1131 was associated with elevated plasma total cholesterol, triglycerides, VLDLc and non-HDLc. Dyslipidemic subjects with TT genotype showed D-Dimer plasma levels significantly increased compared to the C allele. Concerning to hemostatic factors, only dyslipidemic women had a significantly higher level of TAFI as compared to normolipemic women. These results indicates that both APOE and APOA5 -1131T>C polymorphisms may affect plasma lipid-lipoprotein levels in normolipidemic group and in all participants, respectively. Moreover, TAFI plasma levels showed to be correlated to lipid profile variables, suggesting that dyslipidemia exerts some effect on the TAFI synthesis possibly reducing fibrinolysis activity.